1991
DOI: 10.1111/j.1365-2125.1991.tb05622.x
|View full text |Cite
|
Sign up to set email alerts
|

Once vs twice daily administration of a fixed combination of captopril plus hydrochlorothiazide in essential hypertension: a double‐blind crossover study in known responders to a standard combination.

Abstract: The purpose of this randomized, double-blind, crossover trial was to compare the hypotensive effects of a fixed combination of captopril (C) 50 mg and hydrochlorothiazide (HCTZ) 25 mg (C 50/HCTZ 25) once daily with those of a fixed combination of C 25 mg and HCTZ 12.5 mg (C 25/HCTZ 12.5) twice daily. We studied 199 patients (108 M, 91 F) with mild to moderate essential hypertension whose BP was already controlled by the co-administration of C 25 mg and HCTZ 12.5 mg twice daily. They were randomly assigned to e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
2

Year Published

1993
1993
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 15 publications
0
4
0
2
Order By: Relevance
“…Previous studies have reported the incidence of ACE-I induced cough to be as low as 5% 1 to as high as 39%. 2 In the ADOPT and ASCEND trials, it has been reported that the highest incidence of cough is among Asians. 17 The present observation is in agreement with these findings.…”
Section: Incidence Of Cough and No Levelmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have reported the incidence of ACE-I induced cough to be as low as 5% 1 to as high as 39%. 2 In the ADOPT and ASCEND trials, it has been reported that the highest incidence of cough is among Asians. 17 The present observation is in agreement with these findings.…”
Section: Incidence Of Cough and No Levelmentioning
confidence: 99%
“…In spite of their increasing use, these drugs produce various side effects, of which the most troublesome and frequent is the production of persistent dry cough. 1,2 The incidence of ACE-I induced cough has been reported to range between 5% 1 and 39%. 2 Study by Vegter and de Jong-van den Berg 3 suggested that cough as a side effect of ACE-I is being missed and patients are treated with anti-tussive agents with an estimated frequency of 15%.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Em geral desaparece em até quatro dias da sua retirada, porém artigos referem quatro semanas para cessação da mesma. 8 A prevalência da tosse variou no estudo de Rumbolt et al 9 de 0% até 90% no estudo de Lacouciére et al 10 ambos estudos com captopril e enalapril. Na maioria dos estudos a substituição de um IECAs por outro IECAs não resolveu a tosse.…”
Section: < Sumáriounclassified
“…4,5,8 Estudos mais recentes e mais ampliados em termos de população e acompanhamento, bem como duplo cego, dão conta que a tosse varia de 5 a 10%. 14,15 No estudo de Lacourcière et al 10 mostraram em pacientes usando lisinopril a mesma foi retirada e reintroduzida em um estudo duplo cego. Neste caso somente 50% no braço de lisinopril comparado com 29% no braço do losartana (BRA) apresentaram tosse.…”
Section: Epidemiologia Da Tosseunclassified